Comportamento reprodutivo em espécies da tribo Brassolini (Lepidoptera: Nymphalidae): uma revisão bibliográfica - Silva, Matheus Alves da (Universidade Federal de São Carlos, 2023)
Brassolini is a Neotropical butterfly tribe essential to the ecosystems. However, there is a lack of knowledge regarding the species reproductive behavior of this clade. Therefore, this article aims to conduct an extensive bibliographic review and reunite the studies of the last 40 years about the reproductive behavior of Brassolini. Among the 17 genera belonging to the taxon, only 5 had studies regarding their reproduction, with Caligo being the most studied genus, followed by Opsiphanes. In general, even if evolutionarily close, the genera adopt some distinct reproductive strategies regarding the interaction between males and females, mainly due to their anatomical differences. Nevertheless, territoriality is a salient aspect in their reproduction as well coloration indicates significant signaling to the opposite sex, as the blue-violet iridescence in Eryphanis, and in the adaptations for this purpose, as in the eyespots in Caligo. In a nutshell, comprehending the reproductive behavior of this group is crucial in the conservationist aspect, considering that these animals are symbols of beauty and can assist the conservation of other taxons by utilizing them as an umbrella species.
Reproductive behavior in species of the tribe Brassolini (Lepidoptera: Nymphalidae): a bibliographic review
Keywords: Brassolini; Papilionoidea; Satyrinae; Reprodução; Borboletas; Reproduction; Butterfly; CIENCIAS BIOLOGICAS::ZOOLOGIA